Titanium Alloys in Surgical Implants 1983
DOI: 10.1520/stp28942s
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Commercially Pure Titanium and Ti-318 (Ti-6Al-4V) in Orthopedic Implants

Abstract: At the Royal National Orthopaedic Hospital major replacement of long bones began in 1949, and the first titanium-containing endoprosthesis was inserted in 1964. By now over 250 titanium-containing endoprostheses of various kinds have been inserted. Most of these components were made on a modular basis and included sections of cast cobalt-chromium-molybdenum alloy. In 1972 titanium alloy 318 (Ti-318)(Ti-6Al-4V) was introduced, and this alloy largely replaced the previously used commercially pure titanium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…This ability of GPEEK to maintain cell viability and function is reminiscent of other biomaterials, such as the bioactive glasses and the traditional metallic alloys used in orthopedics. 1,2,9,[16][17][18][19][20][21] The osteoblastic MG63 cell line was also shown to flourish on the surfaces of these materials in vitro. [16][17][18][19][20] Although the cell yield from the different GPEEK discs was not significantly different from that of polystyrene, fewer cells were recovered from the discs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability of GPEEK to maintain cell viability and function is reminiscent of other biomaterials, such as the bioactive glasses and the traditional metallic alloys used in orthopedics. 1,2,9,[16][17][18][19][20][21] The osteoblastic MG63 cell line was also shown to flourish on the surfaces of these materials in vitro. [16][17][18][19][20] Although the cell yield from the different GPEEK discs was not significantly different from that of polystyrene, fewer cells were recovered from the discs.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, metallic alloys such as cobalt-chromium-molybdenum (Co-Cr-Mo) and titanium-albumin-vanadium (Ti-6Al-4V) have been used as the materials of choice for orthopedic implants. 1,2 However, metallic alloys are inflexible and have elastic moduli approximately 10-20 times greater than cortical bone. 3 Thus, the implant bears the majority of the load, leaving the bone unstressed.…”
Section: Introductionmentioning
confidence: 99%
“…In the mid-1980s, α + β phase Ti-6Al-4V was commonly regarded as an ideal material for medical implants (Steinemann, 1984;Dobbs and Scales, 1983). However, more recent research has revealed that Ti-6Al-4V debris contains Vanadium, which is harmful to human health (Nichols and Puleo, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Ti(cpi) is used to fabricate implants used in dentistry 4 and maxillofacial reconstruction, 5 as well as to coat devices constructed from titanium alloy. 6 Although Ti(cpi) is not strong enough to be used in orthopedics, 7 the addition of Al and V to Ti creates an alloy with great strength; and together with its low elastic modulus and excellent biocompatibility, 8 this makes it a preferred orthopedic material.…”
Section: Introductionmentioning
confidence: 99%